The Sports Trainers' Level of Understanding of Athlete Development at SKOI East Kalimantan: Tingkat Pemahaman Pelatih Cabang Olahraga Terhadap Pembinaan Atlet Di SKOI Kalimantan Timur - Nanda Alfian Mahardhika; Jeane Betty Kurnia Jusuf; Januar Abdilah Santoso; Galih Priyambada; Julianur (Borneo Educational Journal (Borju), 2022)
This research is a qualitative descriptive study. The purpose of this study was to determine the level of understanding of sports coaches on coaching athletes at the Special School for Internasional Athletes East Kalimantan. The method used is a survei using a questionnaire instrument given to all sports coaches at the Sekolah Khusus Olahragawan Internasional (SKOI) East Kalimantan, totaling 20 coaches. The analytical technique used is descriptive statistics which are stated in the form of percentages. The result showed that 0 trainers or 0,0% were in the very poor category, 2 trainers or 10,0% in the poor category, 2 trainers or 10,0% in the sufficient category, 11 trainers or 55% in the good category, and 5 or 25,5% in the good category. So that it can be explained that the level of understanding of sports coaches on the athlete coaching model at the Sekolah Khusus Olahragawan Internasional (SKOI) East Kalimantan in included in the good category with 11 coaches or 55.0%.